Control and Surveillance in Work Practice: Cultivating Paradox in 'New' Modes of Organizing. Issue 5 (May 2021) - de Vaujany, François-Xavier; Leclercq-Vandelannoitte, Aurélie; Munro, Iain; Nama, Yesh; Holt, Robin
The new world of work is being characterized by the emergence of what are, apparently, increasingly autonomous ways of working and living. Mobile work, coworking, flex office, platform-based entrepreneurship, virtual collaborations, Do It Yourself (DIT), remote work, digital nomads, among other trends, epitomize ways of organizing work practice that purportedly align productivity with freedom. But most ethnographical research already reveals many paradoxical experiences associated with these new practices and processes. Indeed, it appears that with autonomy comes surveillance and control, to a point where, as Foucault observed way back, subjectivity and subject become synonyms, and the current pandemic both strengthens and makes visible this situation. In this introduction to the special issue we make a foray into this situation, using four open and related themes developed in the five papers we selected: managerial control and technology; surveillance and platform capitalism; time and space; and new organizational forms and autonomy. Paradoxical movements are identified for each of them, before we conclude by reflecting on a grounding paradox which appears at the centre of this special issue and the themes it covers.